Secretory meningiomas are defined by combined KLF4 K409Q and TRAF7 mutations - Reuss, David; Piro, Rosario M.; Jones, David T. W.; Simon, Matthias; Ketter, Ralf; Kool, Marcel; Becker, Albert; Sahm, Felix; Pusch, Stefan; Meyer, Jochen; Hagenlocher, Christian; Schweizer, Leonille; et al. (Acta neuropathologica, 2013)
Meningiomas are among the most frequent intracranial tumors. The secretory variant of meningioma is characterized by glandular differentiation, formation of intracellular lumina and pseudopsammoma bodies, expression of a distinct pattern of cytokeratins and clinically by pronounced perifocal brain edema. Here we describe whole-exome sequencing analysis of DNA from 16 secretory meningiomas and corresponding constitutional tissues. All secretory meningiomas invariably harbored a mutation in both KLF4 and TRAF7. Validation in an independent cohort of 14 secretory meningiomas by Sanger sequencing or derived cleaved amplified polymorphic sequence (dCAPS) assay detected the same pattern, with KLF4 mutations observed in a total of 30/30 and TRAF7 mutations in 29/30 of these tumors. All KLF4 mutations were identical, affected codon 409 and resulted in a lysine to glutamine exchange (K409Q). KLF4 mutations were not found in 89 non-secretory meningiomas, 267 other intracranial tumors including gliomas, glioneuronal tumors, pituitary adenomas and metastases, 59 peripheral nerve sheath tumors and 52 pancreatic tumors. TRAF7 mutations were restricted to the WD40 domains. While KLF4 mutations were exclusively seen in secretory meningiomas, TRAF7 mutations were also observed in 7/89 (8 %) of non-secretory meningiomas. KLF4 and TRAF7 mutations were mutually exclusive with NF2 mutations. In conclusion, our findings suggest an essential contribution of combined KLF4 K409Q and TRAF7 mutations in the genesis of secretory meningioma and demonstrate a role for TRAF7 alterations in other non-NF2 meningiomas.